Microinsurance decisions: Gendered evidence from rural Bangladesh - Kumar, Neha; Clarke, Daniel J. (International Food Policy Research Institute, 2014)
This brief summarizes an in-depth study on gendered aspects of willingness to pay for index-based agricultural insurance in Bangladesh.